Rapid climatic events as recorded in Middle Weichselian thermokarst lake sediments - Bohncke, S.J.P.; Bos, J.A.A.; Engels, S.; Heiri, O.; Kasse, C. (Quaternary Science Reviews, 2008)
From a Middle Weichselian sediment sequence in the opencast brown coal mine of Reichwalde (eastern Germany), a ∼40 cm thick thermokarst gyttja deposit has been sampled. The AMS